Research on intelligent computing network technology for large-scale pre-trained models - WANG Xuecong; JI Siwei; LI Cong (Dianxin kexue)
With the development of artificial intelligence, significant achievements are made in various fields such as natural language processing and computer vision through the utilization of large-scale pre-trained models,which promotes the construction of intelligent computing centers. Key technologies related to large-scale pre-trained models in intelligent computing networks were studied. The latest standardization progress of intelligent computing network at home and abroad was systematically reviewed. A target architecture for intelligent computing network was proposed, and the principles of key technologies, including remote direct memory access (RDMA), IB, RoCE, and collective communication, were explored. Moreover, the current issues and future development trends of intelligent computing networks were analyzed. This research holds crucial importance in advancing the development of intelligent computing network technology and providing guidance for the establishment of intelligent computing centers.